Study Models for Chlamydia trachomatis Infection of the Female Reproductive Tract - Jaehyeon Kim; Milena Ślęczkowska; Beatriz Nobre; Paul Wieringa (Microorganisms)
Chlamydia trachomatis (Ct) is a leading cause of sexually transmitted infections globally, often resulting in inflammatory disorders, ectopic pregnancies, and infertility. Studying Ct’s pathogenesis remains challenging due to its unique life cycle and host-specific interactions, which require diverse experimental models. Animal studies using mouse, guinea pig, pig, and non-human primate models provide valuable insights into immune responses, hormonal influences, and disease progression. However, they face limitations in terms of translational relevance due to physiological differences, as well as ethical concerns. Complementing these, in vitro systems, ranging from simple monolayer to advanced three-dimensional models, exhibit improved physiological relevance by replicating the human tissue architecture. This includes the detailed investigation of epithelial barrier disruptions, epithelium–stroma interactions, and immune responses at a cellular level. Nonetheless, in vitro models fall short in mimicking the intricate tissue structures found in vivo and, therefore, cannot faithfully replicate the host–pathogen interactions or infection dynamics observed in living organisms. This review presents a comprehensive overview of the in vivo and in vitro models employed over the past few decades to investigate Ct and its pathogenesis, addressing their strengths and limitations. Furthermore, we explore emerging technologies, including organ-on-chip and in silico models, as promising tools to overcome the existing challenges and refine our understanding of Ct infections.